Convenient syntheses, spectroscopic and structural characterisation of bi-functional boranes - Aldridge, S; Calder, R; Cunningham, M; Malik, K; Steed, J (2000)
The first examples of bi-functional borane derivatives based around a 1,2,4,5-tetrasubstituted benzene framework are reported. Synthesis of ClBO2C6H2O2BCl (4) is accomplished in three steps (69% overall yield) through the intermediacy of the trimethylsilyl derivative 1,2,4,5-(Me3SiO)4C6H2 (3). The bis(borane) species HBO2C6X2O2BH (X=H, 7; X=Cl, 8) on the other hand, can be synthesised in a single step from substituted para-quinone precursors. Crystal structures are reported for compounds 3 and 4. © 2000 Elsevier Science B.V.